Pengaruh Pemberian Jus Jambu Biji (Psidium Guajava L), Terhadap Parameter Histopatologi Radang Kronik dan Ekspresi Vascular Endothelial Growth Factor: Studi Eksperimental Laboratorik pada Adjuvant-Induced Arthritis pada Tikus Wistar - Andika Eka Herlina; Indra Wijaya; Noor Wijayahadi (MEDIA MEDIKA INDONESIANA, 2013)
ABSTRACT The effect of Psidium guajava juice on the histopathologic chronic inflammation parameter and expression of vascular endothelial growth factorBackground: Poliphenol compound and vitamin C in Psidium guajava L has antioxidant, antiinflammation, and antiangiogenic effect. These effects work by inhibiting cytokine, MMP, and VEGF expression. Effects in chronic inflammation histopathological parameter and angiogenic component (VEGF) is not yet known. The objective of the study was to analyze the effect of Psidium guajava L juice on histopathological parameter of chronic inflammation (the depth of cartilage destruction, amount of mononuclear cell, amount of capillary vessel) and VEGF expression in adjuvant-induced arthritis Wistar rats.Methods: It was an laboratory experimental with post test only control group design. Two groups of male Wistar rat, aged 3-4 month, were induced with CFA 0,1 ml twice. After booster on the seventh day, control group was given aquadest, and another group was given Psidium guajava L juice 9 g/15 ml per day, divided into 3 doses for 14 days. Histopathological parameter evaluation and VEGF expression was done in 10 fields view. All data were analysed by T-Test, with level of significant p≤0.05.Result: The amount of mononuclear cell (p=0.000) and capillary vessel (p=0.000) in P group is significantly fewer than K group. The amount of capillary vessel with positive VEGF expression (p=0.138) and size of depth in cartilage destruction (p=0.120) shows no significance difference between two groups. Conclusion: Psidium guajava L juice shows a lowering effect on histopathological parameter of chronic inflammation and VEGF expression in adjuvant-induced arthritis Wistar rats.Keywords: Psidium guajava L, histopathology of chronic inflammation in arthritis, VEGF expressionABSTRAKLatar belakang: Senyawa polifenol dan vitamin C dalam buah Psidium guajava L memiliki efek antiinflamasi, antioksidan, dan antiangiogenik. Ketiga efek ini bekerja melalui penghambatan terhadap sitokin inflamasi, MMP, dan ekspresi VEGF. Efek terhadap parameter histopatologi radang kronik dan komponen angiogenesis (VEGF) pada arthritis belum diketahui. Tujuan: Menganalisis pengaruh jus Psidium guajava L terhadap parameter histopatologi radang kronik berdasarkan ukuran kedalaman destruksi tulang rawan oleh panus, jumlah sel radang mononuklear, jumlah pembuluh darah kapiler dan ekspresi VEGF jaringan sendi adjuvant-induced arthritis tikus Wistar.Metode: Jenis penelitian eksperimental laboratorik dengan desain post test only control group. Tikus Wistar jantan usia 3-4 bulan dibagi 2 kelompok, diinduksi CFA 0,1 ml 2 kali. Setelah hari ke-7 booster, kontrol diberi aquades, perlakuan diberi jus Psidium guajava L 9 g/15 ml per hari dibagi dalam 3 dosis selama 14 hari. Penilaian parameter histopatologi radang kronik dan ekspresi VEGF dilakukan manual dalam 10 lapangan pandang. Dilakukan uji beda T-Test dengan tingkat kemaknaan p≤0,05.Hasil: Pada ukuran kedalaman destruksi tulang rawan, tidak ada perbedaan bermakna antara K dengan P (p=0,120). Jumlah sel radang mononuklear P lebih sedikit secara bermakna dibandingkan K (p=0,000). Jumlah pembuluh darah kapiler P lebih sedikit secara bermakna dibandingkan K (p=0,000). Jumlah pembuluh darah dengan ekspresi VEGF positif tidak ada perbedaan bermakna antara K dengan P (p=0,138).Simpulan: Pemberian jus jambu biji (Psidium guajava L) berpengaruh memperbaiki beberapa parameter radang kronik pada tikus Wistar yang mengalami arthritis.